Studying a (contested/concerned) market in the making: Voluntary offsetting, from UN climate talks to corporate sustainability departments - Véra Ehrenstein; Alice Valiergue (economic sociology_the european electronic newsletter, 2021)
Since the 1990s, carbon markets have been embraced as a policy tool to address climate change. As mentioned by Anita Engels in her editorial to the previous Newsletter, the design of emissions trading markets, where companies buy and sell allowances, requires significant work from legislators and regulators. In economic sociology, carbon markets tend to be associated with the idea of a "government by markets" (Ansaloni, Trompette, and Zalio 2017) and the task of the sociologist is to attend to the interplay between market dynamics and political decision-making (Engels 2006; Mackenzie 2009; Ehrenstein and Neyland, forthcoming).
Keywords: 300